Squad management, injury and match performance in a professional soccer team over a championship-winning season - Carling, C.; Le Gall, F.; McCall, A.; Nedelec, M.; Dupont, G. (European Journal of Sport Science, 2015)
Squad management, injury and physical, tactical and technical match performance were investigated in a professional soccer team across five consecutive league seasons (2008.2013, 190 league games) with specific focus on a championship-winning season (2010/11). For each player, match participation and time-loss injuries were recorded, the latter prospectively diagnosed by the team's physician. Defending and attacking tactical and technical performance indicators investigated included ball possession and possession in opponents' half, passes, forward passes, completed passes and forward passes, crosses and completed crosses, goal attempts and goal attempts on target, successful final third entries, free-kicks and 50/50 duels won/lost. Physical performance measures included total distance and distance covered at high-speeds (.19.1 km/h). Results showed that during the 2010/11 season, squad utilisation was lowest potentially owing to the observed lower match injury occurrence and working days lost to injury thereby increasing player availability. In 2010/11, the team won both its highest number of points and conceded its lowest number of goals especially over the second half of this season. The team also won its highest number of games directly via a goal from a substitute and scored and conceded a goal first on the highest and lowest number of occasions, respectively. While multivariate analysis of variance (MANOVA) detected a significant difference in some attacking and defensive performance indicators across the five seasons, these were generally not distinguishing factors in 2010/11. Similarly, univariate ANOVAs showed a significant difference in running distances covered across seasons, but the trend was for less activity in 2010/11.